2007
DOI: 10.2174/157341107779314253
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteome and Kinome Analysis: Unique Perspectives on the Same Problem

Abstract: Since ancient times many natural organic materials have been used in artistic and historic works as binders, adhesives, fillers and coatings. The identification of these materials is important not only for a proof of authenticity; for restorers and conservators it is essential to recognize the materials and technologies employed by artists and craftsmen. For identification and characterisation of the different natural organic binders spectrometric and chromatographic methods are well established. Recently, cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…Blastp results revealed that about half of the bovine sequences had 100% identity to the query sequences and that the majority of the remaining peptides had limited sequence divergence (Table 1). A comparison of the protein descriptions for the query and hit sequences confirmed that they referred to orthologous proteins (19). These results indicate that phosphorylation sites between human and bovine orthologous proteins are not absolutely conserved, which suggests that a human array would be of limited value for bovine kinome analysis.…”
Section: Introductionmentioning
confidence: 76%
“…Blastp results revealed that about half of the bovine sequences had 100% identity to the query sequences and that the majority of the remaining peptides had limited sequence divergence (Table 1). A comparison of the protein descriptions for the query and hit sequences confirmed that they referred to orthologous proteins (19). These results indicate that phosphorylation sites between human and bovine orthologous proteins are not absolutely conserved, which suggests that a human array would be of limited value for bovine kinome analysis.…”
Section: Introductionmentioning
confidence: 76%
“…Thus, we employed systems kinomics (20,29,30) with high-throughput human kinome peptide arrays to study the global activation state of host kinases, the kinome, following West African or Congo Basin MPXV infection. The resultant kinome data sets were subjected to hierarchical cluster analysis for comparative analysis and visualization of changes to host cell phosphorylation following infection.…”
Section: West African and Congo Basin Mpxv Induce Differentialmentioning
confidence: 99%
“…A number of experimental approaches are available for the analysis of phosphorylation based cellular signaling, these can be divided into two groups, phosphoproteome and kinome analysis 16. The difference is dependent on whether the consideration is on the protein kinases that phosphorylate proteins, the kinome, or the targets of these enzymes, the phosphoproteome.…”
Section: Introductionmentioning
confidence: 99%
“…This is exacerbated by the fact that these proteins, in addition to being found in low abundance, are often phosphorylated at sub‐stoichiometric levels. This means that a small fraction of a given signaling protein is phosphorylated at any one time; only 1–2% of the total individual protein compliment of a cell is found in the phosphorylated form 16–19. When considering all these experimental limitations, a promising alternative for characterization of cellular phosphorylation is to focus instead on the kinome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation